MOLECULAR CLONING, PROKARYOTIC EXPRESSION AND PREPARATION OF ANTISERUM AGAINST LILY SYMPTOMLESS VIRUS TGB1 PROTEIN - Xu, Pinsan; Wang, Xinlei; Zhang, Zhengyao (JOURNAL OF ADVANCES IN AGRICULTURE, 2017)
The triple gene block gene TGB1 was amplified by RT-PCR from lily leaves infected with Lily symptomless virus and cloned into prokaryotic expression vector pET-28a(+). The recombinant vector was transformed into Escherichia coli strain BL21 (DE3). On induction with isopropyl Î²-D-1-thiogalactopyranoside,TGB1 protein was highly expressed and the molecular weight was 29 kDa (including a His-tag-containing fusion). After protein purification by Ni2+-NTA affinity chromatography, a polyclonal antibody against TGB1 was raised in mouse. Western blot analysis showed that the antiserum reacted specially with the TGB1 protein of LSV. ELISA and RT-PCR confirmed that the antiserum reacted specially with lily leaves infected with LSV, and can be used for a rapid test for LSV. The antibody produced in this work may be used for future immunohistochemistry and functional study of TGB1.